Comparative Ability of Mesenchymal Stromal Cells from Different Tissues to Limit Neutrophil Recruitment to Inflamed Endothelium. - Hafsa Munir; Nguyet-Thin Luu; Lewis S C Clarke; Gerard B Nash; Helen M McGettrick (PLoS ONE)
Mesenchymal stromal cells (MSC) are tissue-resident stromal cells capable of modulating immune responses, including leukocyte recruitment by endothelial cells (EC). However, the comparative potency of MSC from different sources in suppressing recruitment, and the necessity for close contact with endothelium remain uncertain, although these factors have implications for use of MSC in therapy. We thus compared the effects of MSC isolated from bone marrow, Wharton's jelly, and trabecular bone on neutrophil recruitment to cytokine-stimulated EC, using co-culture models with different degrees of proximity between MSC and EC. All types of MSC suppressed neutrophil adhesion to inflamed endothelium but not neutrophil transmigration, whether directly incorporated into endothelial monolayers or separated from them by thin micropore filters. Further increase in the separation of the two cell types tended to reduce efficacy, although this diminution was least for the bone marrow MSC. Immuno-protective effects of MSC were also diminished with repeated passage; with BMMSC, but not WJMSC, completing losing their suppressive effect by passage 7. Conditioned media from all co-cultures suppressed neutrophil recruitment, and IL-6 was identified as a common bioactive mediator. These results suggest endogenous MSC have a homeostatic role in limiting inflammatory leukocyte infiltration in a range of tissues. Since released soluble mediators might have effects locally or remotely, infusion of MSC into blood or direct injection into target organs might be efficacious, but in either case, cross-talk between EC and MSC appears necessary.